Survey of Employees' Safety Attitude in a Teaching Hospital Tehran 2010 - M. Mahmmoudi; L. Azimi; P. Raessi; M.R. Maleki; A.A. Nasiripour; J. Tabibi (Salāmat-i kār-i Īrān, 2011)
Background and aimsThe Medical Errors and the potential unsafe actions are always regarded as a serious trouble by the managers and health care providers. Using the employees' attitude data as a measurement criterion in the evaluation of the hospitals performance in the field of the “Safety” can improve the safety level among the personnel and patients . Survey of employees' attitude about safety and its comparison with different groups of offering health services in a teaching Hospital was the main objective of present study.   MethodsIn order to specify patient safety culture in Moddares hospital, all employees including physicians, nurses, managers and employees of Para-clinic, a volume sample consisting of 212 persons were selected. Then it was used from questionnaire of safety attitude within 6 dimensions including Teamwork climate, Safety climate, perceptions of Management , Job Satisfaction, Working Conditions and Stress Recognition. At first this questionnaire was gone under assessing validity and trust. The scale of measuring, Likert was 5 grades. In order to specify difference between groups under study it was used from ANOVA test.   Results Positive safety culture within 6 dimensions including Teamwork Climate, Safety climate, Job Satisfaction, Stress Recognition, Perception of Management , Working Conditions for doctors were 3, 4.13, 17.4, 0, 4.3, and 8.7 respectively; the aforesaid Dimensions for nurses were 19, 2.6, 10.3, 7.8, 2.6 and 15.5 respectively, the aforesaid Dimensions for managers were 30.3, 6.1, 33.3, 0, 18.2 and 21.2 respectively and the aforesaid Dimensions for employees of Para-clinic Were 50, 12.5, 25, 12.5, 10 and 37.5 respectively. There was Significant difference from View Point of statistics (p<0.5) from Dimensions of Job satisfaction among managers and nurses, employees of Para-clinic and nurses this difference Were zero and 0.001. From View Point of Stress recognition among managers and employees of Para-clinic , managers and nurses, employees of Para-clinic and doctors were 0.062, 0.022 and 0.047 and from View Point of Perceptions of management the level of this difference among managers and nurses was 0.002. Meanwhile all employees under study had similar View Point toward teamwork Climate, safety Climate and Working Conditions.   Conclusion It recommended that health services managers and employees improve patient safety culture in their organizations and in order to can use of: to show senior leadership's willingness to safety, Developing a system for event reporting and Improving teamwork.